2015
DOI: 10.1016/j.foodchem.2014.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterisation of wheat bran oil-in-water nanoemulsions

Abstract: 9Wheat bran oil (WBO) has been reported to have an important content of bioactive 10 compounds such as tocopherols, alkylresorcinols, steryl ferulates and other phenolic 11 compounds; however, its poor solubility in water systems restricts its applications in the food 12 industry. This study is focused on the formulation of oil-in-water (O/W) nanoemulsions of 13 WBO in order to improve the bioaccessibility of its active compounds. The influence of oil 14 concentration, surfactant type and concentration, and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 29 publications
9
56
2
3
Order By: Relevance
“…The globule size of the investigated systems, measured after dilution with (1:100) [38], shows a 235 range of 44-105 nm ( Table 2) [39]. It was also demonstrated that the higher the oil/surfactant ratio, the higher the droplet size [40].…”
Section: Preparation Of Nanoemulsion Systemsmentioning
confidence: 74%
See 1 more Smart Citation
“…The globule size of the investigated systems, measured after dilution with (1:100) [38], shows a 235 range of 44-105 nm ( Table 2) [39]. It was also demonstrated that the higher the oil/surfactant ratio, the higher the droplet size [40].…”
Section: Preparation Of Nanoemulsion Systemsmentioning
confidence: 74%
“…Hence, zeta potential is an indication of repulsive forces between emulsion droplets. Large values (positive or negative) indicate difficulty of coalescence of droplets and therefore high emulsion stability [38]. Zeta potential values of NEs indicate acceptable to good stability [42].…”
Section: Preparation Of Nanoemulsion Systemsmentioning
confidence: 99%
“…Fibres, lignins, oligosaccharides, polyphenols, lignans, phytic acid, minerals, alkylresorcinols, glutathione, sulphur compounds, α-linoleic acid, carotenoids, vitamin B and E have been identified as the major components. Wheat bran oil contains tocopherols, alkylresorcinols, steryl ferulates and other phenolic compounds (Rebolleda et al, 2015). It was reported that arabinoxylan oligosaccharides extracted from wheat bran constitutes a promising prebiotic nutrient in the control of obesity and related metabolic disorders.…”
Section: Wheat (Triticum Spp)mentioning
confidence: 99%
“…For pulsed DC electric fields, the two fundamental processes of water droplet growth are migratory coalescence and dipole coalescence (Urdahl, et al, 1996). In addition, dielectrophoresis coalescence is also important for cylindrical electrodes (Rebolleda et al, 2015) because of the non-uniform electric field.…”
Section: Introductionmentioning
confidence: 99%